Economia das disposições : relações de relevância e reconhecimento numa abordagem das mulheres no Espiritismo - Alves, Cristiano Evaristo da Rosa (2016)
We seek to unify two theories under a common north: the Recognition Theory (Honneth) and the Theory of Relevance (Rauen, Campos, Sperber and Wilson), or a cognitive-communicative contribution to recognition relations. This contribution takes into account and partially systematize the issue of energy of the subjects based on their relevance set, which are the aspects that anchor cognition. Thus, the recognition process would be linked in some way to offset that particular stimulus produces. Love would be the main stimulus, in recognition sphere, being responsible for others: law and solidarity (or social contributions), to be compensatory. Even we defend love as the genesis of democracy. In this sense, we seek the elements of recognition of Axel Honneth in Spiritist Doctrine, using the analytical method we call the scheme of the provisions, to assess the provisions and / or energies of people and institutions to women within the Spiritism, where we use quantitative sampling (data by sex of command posts), qualitative (interviews), bibliographic and documentary research. The spiritist movement of Rio Grande do Sul (State of Brazil) had in 2015, among its 406 societies in the sample, 51% of women were in the presidency. We identify elements that support the Honneth's thesis that the substantiation practices in the spheres of love, law and solidarity, shapes the social praxis of this religious movement in an milieu with very symmetrical relations between men and women, with effective participation in policy formation of the community will, ensuring not only autonomy but somehow female individuation.